Sympathetic reinnervation and heart rate variability after cardiac transplantation. - Lord, S. W. (1997)
BACKGROUND: Heart rate variability is thought to measure autonomic modulation, but the relation has never been demonstrated directly in humans. AIM: To test the hypothesis that increased low frequency heart rate variability reflects sympathetic reinnervation after cardiac transplantation. PATIENTS: 24 cardiac transplant recipients at the time of routine surveillance coronary angiography two or more years after cardiac transplantation, and 10 controls with normal coronary arteries undergoing angiography for investigation of chest pain. SETTING: Regional cardiothoracic centre. METHODS: Sympathetic effector function at the sinus node was assessed by measuring the fall in cycle length for two minutes after injection of tyramine to the artery supplying the sinus node. Heart rate variability was measured from three-minute RR interval sequences at rest, during metronomic respiration, and before and after atropine. RESULTS: The logarithm of the low frequency component of heart rate variability during metronomic respiration was linearly related to the logarithm of the change in cycle length after injection of tyramine (R2 = 0.28, P = 0.007). Absolute units more accurately reflected sympathetic effector function than did normalised units or the ratio of low frequency to high frequency. Atropine did not affect high frequency heart rate variability in transplant recipients. CONCLUSIONS: The low frequency component of heart rate variability is directly related to sympathetic reinnervation to the sinus node.